Analysis of Factors Affecting Credit Access and Its Impact on SHallot Production in Manggarai District Using The Heckman Selection Model - Utami, Dewanti Risa; Prasetyo, Kunandar; Cordanis, Astried Priscilla (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Shallot is an agricultural product that contributes greatly to the Indonesian economy. One of the main problems in shallot farming is the low ability of farmers to access credit. The purpose of this study is to determine the factors that influence access to credit and understand the impact of credit on shallot production in Manggarai Regency. This study was conducted in Reok District, Manggarai Regency. The study site was specifically chosen taking into account that Reok District is the only shallot development area in Manggarai Regency. The sampling technique in this study used proportional quota sampling. The sample consisted of 50 farmers, consisting of 30 farmers who did not have access to credit, and 20 farmers who had accessed credit. The data analysis method used in this study is the Heckman selection model. The analysis of the Heckman selection model consists of two phases of analysis, namely the selection equation and the outcome equation. Based on the results of the analysis of the Heckman selection model, it is found that the factors that have a real impact on the credit availability of shallot farmers in Manggarai Regency are age, education, land area, number of household members and membership of farmer groups. farmers. In the second phase (outcome's equation), it is known that shallot production is significantly affected by labor input, pesticides and the amount of credit.  Research findings indicate a positive correlation between enhanced credit access and increased shallot production. Facilitating credit access for farmers can be a significant policy intervention to stimulate shallot production in Manggarai Regency. Therefore, initiatives are necessary to promote credit accessibility, especially from formal financial institutions.